Pengaruh Kepercayaan dan Kepuasan Pelanggan terhadap Loyalitas Pelanggan pada AP Garage (Bengkel Cat & Custom) - Aris Ramadhany; Supriyono Supriyono (Universitas Batanghari Jambi, 2022)
This study aims to analyze and examine the effect of trust and customer satisfaction on customer loyalty at AP Garage (Paint & Custom Workshop). The population of this research is AP Garage (Paint & Custom Workshop) customers who have used the services of AP Garage (Paint & Custom Workshop) at least twice. The sample of this study was determined using non-probability sampling so as to produce 50 respondents. The results in this study indicate that trust contributes positively to AP Garage's customer loyalty, the higher the customer's trust in a service, the higher the level of customer loyalty to the service. For customer satisfaction, it is known to contribute positively to customer loyalty. If the customer is satisfied, the customer will not move to another place and will not be reluctant to take advantage of the services that have satisfied him.